Composition of School Meals in Sweden, Finland, and Iceland: Official Guidelines and Comparison With Practice and Availability. (10th September 2018) - Juniusdottir, Ragnheidur; Hörnell, Agneta; Gunnarsdottir, Ingibjorg; Lagstrom, Hanna; Waling, Maria; Olsson, Cecilia; Talvia, Sanna; Olafsdottir, Anna S.
ABSTRACT: BACKGROUND: Nutritious and attractive school meals can improve health equality and public health. Current official guidelines and recommendations on food and nutrient composition of school meals in 3 Nordic countries; Sweden, Finland, and Iceland, are described and compared with actual practice, ie, availability of foods and nutrients in served reference meals in 3 selected areas in each country. METHODS: A country comparison was made between official guidelines, and actual practice was studied in participating schools. Reference portions of school meals (N = 170) provided in 24 compulsory schools were photographed and weighed. Food and nutrient availability were compared with official guidelines in each country. RESULTS: Emphasis of recommendations on whole‐grain bread in Sweden, whole grains in Finland, and fish in Iceland were reflected in food availability. The energy content of the meals provided was lower than guidelines and there was a large variation in energy content between days. CONCLUSIONS: The guidelines regarding food availability were quite well followed, but the large variation in energy and nutrient content of provided school meals between days indicates a need for standardization.